A Severe Case of Lymphomatoid Papulosis Type E Successfully Treated with Interferon-Alfa 2a - Aslı Bilgiç Temel; Betül Unal; Hatice Erdi Şanlı; Şeniz Duygulu; Soner Uzun (Hindawi Limited, 2017)
Lymphomatoid papulosis (LyP) is a benign papulonodular skin eruption with histologic features of malignant lymphoma. A new variant of LyP which was termed "type E" was recently described with similar clinical and histological features to angiocentric and angiodestructive T-cell lymphoma. LyP type E is characterized with recurrent papulonodular lesions which rapidly turn into hemorrhagic necrotic ulcers and spontaneous regression by leaving a scar. None of the available treatment modalities affects the natural course of LyP. For therapy various modalities have been used such as topical and systemic steroids, PUVA, methotrexate, bexarotene, and IFN alfa-2b. Here we present a severe and devastating case with a very rare variant of LyP type E, which is, to our knowledge, the first case successfully treated with IFN alfa-2a. Now disease has been maintaining its remission status for six months.